Design, modeling and control of a miniature bio-inspired amphibious spherical robot - Xing, Huiming; Shi, Liwei; Hou, Xihuan; Liu, Yu; Hu, Yao; Xia, Debin; Li, Zan; Guo, Shuxiang (Mechatronics (Oxford), 2021)
•A bio-inspired amphibious robot with Legged, Water-Jet Composite Driving Mechanism.•A D-H-based kinematic model, gait design and gait adjustment on a slope.•“H” mode and “工” mode decrease the turning time effectively.•Real-time dynamic thrust vectoring allocation strategy for 3-D control.•Launch and land autonomously in amphibious area. It is a huge challenge for an amphibious robot with a high locomotory performance to locomote in amphibious environments, including crawling on rough terrains, maneuvering underwater, and launching and landing motion between land and water. To deal with such a challenge, a miniature bio-inspired Amphibious Spherical Robot (ASRobot) with a Legged, Multi-vectored Water-jet Composite Driving Mechanism (LMWCDM) has been designed. In this paper, locomotory performance of the robot in amphibious field environments is studied. First, a simplified kinematic model was built to study crawling gaits, and with an online adjustment mechanism, the gaits were adjusted, enabling the robot to climb up slopes more stably. Then, using a dynamic underwater model, a real-time dynamic thrust vectoring allocation strategy is proposed to generate the water-jet thrust and joint angles using desired forces and torques computed by four parallel PID algorithms. Finally, a set of experiments were carried out to evaluate the performance of on land locomotion and underwater locomotion. Further, outdoor locomotion experiments including crawling on various terrains, launching and landing motion, were conducted in field environments. The results demonstrate that the robot prototype possesses the high locomotory performance which endows its wide application of disaster rescue, reconnaissance and resource exploration in amphibious environments.